SOSIALISASI NILAI BUDAYA DALAM KELUARGA DI LINGKUNGAN ETNIS BUNGKU - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT This study discusses about a socialisation of cultural values in Bungku ethnic. The aim is to verificate family influence in the growth of cultural values on the next generation, by using the method and media, and what crucial values that a child must have before to be an adult. The research can express that Bungku people have a parental and bilateral clan system through descendental line from two sides, father and mother. Therefore family has a same function and role in the making of child personal, but the main holder is father and the main executor is mother. All cultural value concepts as ethic, otonomy, loyalty to parents, .diciplinary, responsibility, honesty and obedience have a same position in the daily personal behaviour. Media that used here are floklore, playing and customary ceremonies. To teach the child for practicing customary rules, sanctions must be given as sinepi (bit on hip), binosi or pirwe biri (to pull a ear), inukopi or ginintai fifilul (pleated or to take pepper into the mouth), tinonto7npa,a (to pinch a thigh) and so on. Keywords: socialization -- cultural values Bungku family ,